Associação entre composição domiciliar e padrões alimentares em adolescentes - Leite, Jéssica Almeida (2021)
The dietary pattern among adolescents has been characterized by the choice of foods that mark unhealthy eating, which represents an important risk factor for obesity and other chronic non-communicable diseases. A household composition is considered an important context capable of influencing adolescent food consumption. This work consists of a manuscript and an original analysis based on data obtained through the Cardiovascular Risk Study in Adolescents (ERICA). The manuscript aimed to analyze the association between household composition and dietary pattern in adolescents, through a systematic review of the literature. Eleven articles were included according to search strategy and eligibility criteria following the PROSPERO protocol. The evaluated studies show that adolescents who lived with both parents had a higher frequency of consumption of vegetables and breakfast. Healthier food preferences were found among adolescents living in nuclear families and irregular consumption of breakfast and unhealthy food markers were observed among adolescents living in single-parent households, with a reconstituted family and extended families. Additionally, a nationally representative sample was evaluated, with 71,740 adolescents aged 12 to 17 years participating in ERICA, conducted in 2013-2014, with the aim of analyzing the association between household composition and dietary patterns in Brazilian adolescents. Five dietary patterns were identified, the first pattern, called “Traditional” consisting of rice and preparations, beans and legumes and red meat, presenting a negative charge for pasta and preparations. The second standard, named “Lanches”, was made up of breads, oils and fats, cheeses, coffee, and processed meats. The third called “white meat” was composed of poultry and fish, with a negative charge for red meat. The fourth standard room, named “Ultra-processed”, consisting of drinks with added sugar, snacks, sweets and added sugar, with a negative charge for coffee. The fifth food standard called "Minimally processed" was composed of fruits, milk and dairy products, vegetables and cereals and oilseeds. It was possible to verify that the fact of living with both parents or only with the mother did not change the dietary patterns found among these household compositions. Living without a father and mother is associated with eating patterns composed of food groups that are considered unhealthy. The dietary patterns of adolescents who live with their father alone are marked by lower consumption of ultra-processed foods and higher consumption of foods considered healthier. Household composition can be complex and can influence adolescent food consumption, emphasizing the importance of incorporating home composition in initiatives aimed at adolescent eating and health habits.